The Use of Computer-aided Design and 3-Dimensional Models in the Treatment of Forearm Malunions in Children. Issue 1 (March 2015) - Storelli, Dora A.R.; Bauer, Andrea S.; Lattanza, Lisa L.; McCarroll, H. Relton
Abstract : Computer-aided design has several orthopedic applications. In this article we propose the use of computer-aided design to address the problem of forearm malunions in children. Traditional methods of planning forearm osteotomies utilize 2-dimensional radiographs, however, this is not a reliable method to address rotational deformities. Our method involves collaboration with clinical engineers at Materialise (Leuven, Belgium) to produce patient-specific cutting jigs using preoperative computed tomographic scans and 3-dimensional printing technology. This method allows for precise planning of complex and multiple osteotomies while decreasing the need for intraoperative decision making. Our initial results with this technique demonstrate improvements in forearm rotation and distal radioulnar joint stability.